2001
DOI: 10.1046/j.1440-1746.2001.02515.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum type IV collagen test in comparison with platelet count for predicting the fibrotic stage in patients with chronic hepatitis C

Abstract: The serum type IV collagen test was slightly superior to the platelet count for assessing the fibrotic stage in patients with chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 26 publications
4
43
0
1
Order By: Relevance
“…Serum C-IV has been used to diagnose liver fibrosis in diseases that evolved with sinusoid capilarisation (Hiramatsu et al 1995, Murawaki et al 2001, pereira et al 2004, Santos et al 2005, Halfon et al 2006, Yoneda et al 2007). Comparing serum C-IV levels between groups, according to the clinical classification of patients with mansonic and hematobic schistosomiasis, Shahin et al (1992) found high serum levels in patients with hepatosplenic schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum C-IV has been used to diagnose liver fibrosis in diseases that evolved with sinusoid capilarisation (Hiramatsu et al 1995, Murawaki et al 2001, pereira et al 2004, Santos et al 2005, Halfon et al 2006, Yoneda et al 2007). Comparing serum C-IV levels between groups, according to the clinical classification of patients with mansonic and hematobic schistosomiasis, Shahin et al (1992) found high serum levels in patients with hepatosplenic schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos têm utilizado o AH como preditor de fibrose nos pacientes com HCC (7,12,13,15,27) . Nossos achados corroboram os de Halfon et al (7) , que reuniram 405 portadores de HCC para avaliar a acurácia desse marcador em predizer o estádio da fibrose hepática, e concluíram que o AH poderia ser usado clinicamente como marcador não-invasivo para fibrose e/ou cirrose.…”
Section: Discussionunclassified
“…These include: glycoproteins, such as serum hyaluronate [13][14][15][16][17], laminin [18,19], and YKL-40 [20]; the collagens family, such as procollagen III N-peptide (PIIINP) [13] and type IV collagen [21]; collagenases and their inhibitors, such as matrix metalloproteases (MMP) [22] and tissue inhibitory metalloprotease-1 (TIMP-1) [23].…”
Section: Biological Approach: Serum Fibrosis Biomarkersmentioning
confidence: 99%